Synthesis of novel sulfide-based cyclic peptidomimetic analogues to solonamides - Brango-Vanegas, José; Martinho, Luan A.; Bessa, Lucinda J.; Vasconcelos, Andreanne G.; Plácido, Alexandra; Pereira, Alex L.; Leite, José R. S. A.; Machado, Angelo H. L. (Beilstein Journal of Organic Chemistry, 2019)
Eight new sulfide-based cyclic peptidomimetic analogues of solonamides A and B have been synthesized via solid-phase peptide synthesis and SN2’ reaction on a Morita–Baylis–Hillman (MBH) residue introduced at the N-terminal of a tetrapeptide. This last step takes advantage of the electrophilic feature of the MBH residue and represents a new cyclization strategy occurring. The analogues were prepared in moderate overall yields and did not show toxic effects on Staphylococcus aureus growth and were not toxic to human fibroblasts. Two of them inhibited the hemolytic activity of S. aureus, suggesting an interfering action in the bacterial quorum sensing similar to the one already reported for solonamides.
Keywords: antivirulence drug; bacteria; macrocyclization; pathoblocker; quorum quenching